La discriminación racial, étnica y social en el Perú: balance crítico de la evidencia empírica reciente - Santos, Martín (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
There is a growing interest in studying discrimination in Peruvian Social Science. Against this backdrop, this article seeks to assess critically recent empirical research on discrimination in Peru, with an emphasis on racial, ethnic and social discrimination in employment and income, firms, health organizations, education, relationship with public agencies and everyday life. After reviewing the relevant literature on discrimination, this article presents a critical appraisal, taking into consideration the research questions posed, the theoretical frameworks and analytical categories used, the ways in which the notion of «race» is measured, the questions asked to measure discrimination, the manners in which discrimination is detected, and the (debatable) ways researchers interpret their findings. The articleconcludes by highlighting gaps in the literature which should be addressed.

La discriminación, en tanto fenómeno social, constituye un tema de creciente interés en las ciencias sociales peruanas. En este contexto, el presente artículo tiene como objetivo principal realizar una evaluación crítica de esta literatura, poniendo énfasis en la discriminación racial, étnica y social. En la primera parte de este trabajo se presenta la literatura relevante en los siguientes ámbitos: empleo e ingresos, empresa, salud, educación, relación con entidades públicas y vida cotidiana. En la segunda parte se realiza una evaluación crítica, teniendo en cuenta los siguientes ejes: las preguntas de investigación, las perspectivas teóricas y las categorías conceptuales, la forma de medir el concepto de «raza», las preguntas que se plantean para medir el concepto de discriminación, las formas de identificar la existencia de discriminación y las interpretaciones (discutibles) que se hacen de los resultados obtenidos. El artículo concluye sugiriendo vacíos en la literatura, los cuales deben ser atendidos.
Racial, ethnic and social discrimination in Peru. A critical assessment of recent empirical research
Keywords: Discriminación; Estereotipo; Prejuicio; Raza; Exclusión Social; Sociology; Discrimination; Stereotype; Prejudice; Race; Social Exclusion; https://purl.org/pe-repo/ocde/ford#5.04.00